2017
DOI: 10.1111/tid.12800
|View full text |Cite
|
Sign up to set email alerts
|

Early pneumopericardium after heart transplantation

Abstract: A 60-year-old woman with a history of dilated cardiomyopathy underwent heart transplantation. One month post discharge, she presented to clinic with low-grade fever and productive cough. Her chest radiograph showed air-fluid levels in the pericardial silhouette. Transthoracic echocardiogram showed a large complex pericardial collection with no evidence of cardiac tamponade. The patient was urgently taken to the operating room for exploration. A large "egg-shaped" mass in the pericardium measuring 10 × 12 cm wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Moreover, younger ages, as well as history in the use of ventilator and ECMO were acompanied by higher risks of infection causing high mortality rates [64]. In addition, a case report showed that Enterobacter cancerogenous could be identified in heart transplant recipients leading to early pneumopericardium [65]. Severe gastroparesis is a rare condition that could be diagnosed in recipients of orthotopic heart transplantation leading to significant morbidity, including vomiting, aspiration, and pneumonia [66].…”
Section: Deep Sternal Wound Infection and Other Infectionsmentioning
confidence: 99%
“…Moreover, younger ages, as well as history in the use of ventilator and ECMO were acompanied by higher risks of infection causing high mortality rates [64]. In addition, a case report showed that Enterobacter cancerogenous could be identified in heart transplant recipients leading to early pneumopericardium [65]. Severe gastroparesis is a rare condition that could be diagnosed in recipients of orthotopic heart transplantation leading to significant morbidity, including vomiting, aspiration, and pneumonia [66].…”
Section: Deep Sternal Wound Infection and Other Infectionsmentioning
confidence: 99%